(untitled) (Minerva, 2019)
The epigraphical set of Vellica (Olleros de Pisuerga, Palencia) allows comparisons to be made with those of Asturica Augusta and Clunia. If these sets have been chosen, it is because they are so different among themselves. Some of them are capitals of Conventus Iuridicus, characterised by the economic activity, emigration and the highly-qualified civil servants of the Imperial Administration; whereas the one from Vellica is typical of a native town, allowing the establishment of correlations not only with regard to socio-economic characteristics but al so regarding typological and ornamental elements. This differentiates an Epigraphy developed in administrative towns from an Epigraphy made in a town with a strong native component.